The logging recognition of solid bitumen and its effect on physical properties, AC, resistivity and NMR parameters. (February 2020) - Li, Yong; Chen, Shijia; Lu, Jungang; Wang, Gang; Zou, Xianli; Xiao, Zhenglu; Su, Kaiming; He, Qingbo; Luo, Xingping
Abstract: Solid bitumen not only strongly damages the reservoir properties, but it is easily confused with oil and gas in the conventional classification logging interpretation, which seriously affects the effective recognition of oil and gas. Thus, it leads to a deceptive estimation of the reserve. Focusing on the above problems, this study takes Jurassic solid bitumen-containing reservoirs from the Santai-Northern Santai area in the Junggar Basin as an example, and aims to quantitatively evaluate the impact of solid bitumen on the porosity, permeability, resistivity, AC (Acoustic) and NMR (Nuclear Magnetic Resonance), with a comparison between the values of these parameters before and after core bitumen dissolution, as well as to establish an NMR identification method for solid bitumen. The results show that solid bitumen can damage the pore structure of the reservoir and cause a reduction of porosity and permeability. The content of solid bitumen is linearly correlated with the change of porosity and permeability. After solid bitumen dissolved, the resistivity decreased, the longitudinal wave time difference (Vp) and shear wave time difference (Vs) increased, and the shear wave time difference changed noticeably. The content of solid bitumen is exponentially correlated with the change of resistivity, and linearly correlated with the change of longitudinal wave time difference and shear wave time difference. Solid bitumen had a short transverse relaxation time and a response range of 10–1000 μs (Peak 1) on the T2 map. Bitumen-containing sandstone had 3 peaks on the T2 map. Peak 1 decreased, while Peaks 2 and 3 increased after the solid bitumen dissolved. Solid bitumen can be characterized by a typical short time lag of the transverse wave, a bigger density porosity than the NMR porosity and small values of T1LM and T2LM, which led to an effective recognition of the layers of solid bitumen. The results are significant for the exploration and development of oilfields. Highlights: The linear relationship between bitumen content, porosity and permeability is established. The relation of solid bitumen on the AC and Resistivity was established. We point out the response characteristics of solid bitumen in NMR logging. The logging identification method for solid bitumen was established, which was important for the logging interpretation.